Perencanaan Biaya Reklamasi Pada Lahan Bekas Penambangan Batubara Di Site MTBU PT Bukit Asam Tbk Kabupaten Muara Enim - Nadilah Juang Putri; Franto Franto; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2022)
PT Bukit Asam Tbk is a coal mining company. The ex-mining area of ​​the MTBU site which will be reclaimed in accordance with the 2020 plan is 44 ha, but the available land is only 24.84 ha, the rest is still considered productive for mining. Therefore, it is necessary to study the planning of reclamation costs on the MTBU site land. The method of this research activity begins with determining the area of ​​the site to be reclaimed using Argics 10.6 software. then the reclamation costs were calculated which were grouped into direct costs and indirect costs based on KEPMEN ESDM 1827 of 2018. The results of the calculation of the direct cost components and indirect costs of the reclamation plan activities covering an area of ​​24.84 ha, namely the direct cost of reclamation of Rp. 14,857,849,955 with details of land management costs of Rp 2,363,798,980 and revegetation costs of Rp 485,597,426. Indirect costs are Rp 3,179,579,890,37 with details of equipment mobilization and demobilization costs (2.5%) of Rp 371.446248.88, reclamation planning costs (6%) of Rp 891.470.997.30, administrative costs and profits third parties as the implementation of the reclamation stage of production operations (8.5%) amounting to Rp. 1,262,917,246.18 and supervision fees (4.4%) of Rp. 653,745,398.02. The total cost required for land reclamation of 24.84 ha is Rp. 18,037,429,845.37.